A Study on DNA Fingerprinting Using Various Human Samples - Dülger, Hikmet Ergin; Tokdemir, Mehmet; Erbağ, B.; Atalay, Erol Ömer; Doymaz, Mehmet Ziya (The Bulletin of Legal Medicine, 1997)
In recent years DNA fingerprinting has shown a great potential for the identification of samples obtained in the fields of forensic medicine. The aim of the study was the utilization of different biological material in DNA fingerprinting technique. In this study, three DNA samples obtained from different tissues of 3 individuals who were non-related to each other were examined. The DNA samples were extracted from blood, root of hair, saliva, semen and finger nails. The quantity of DNA obtained from semen samples were the greatest (4.46pg). The least DNA extraction was realized from saliva and fingernails (respectively 0.82pg and 0.90pg). The results of Polymerase Chain Reaction (PCR) carried out with human tandem repeat specific primers indicated that regardless of the tissue from which DNA was extracted, PCR amplified products from the same individual exhibited an identical migration pattern on 1.4% agarose gel electrophoresis. However migration patterns differed in samples whose DNA was extracted from different individual. As a preliminary study, the results have shown that the application of DNA fingerprinting technique could be possible in Elazığ.Keywords: Forensic medicine, DNA fingerprinting, DNA isolation
Keywords: forensic medicine; DNA fingerprinting; DNA isolation